2013
DOI: 10.1063/1.4792732
|View full text |Cite
|
Sign up to set email alerts
|

In-situ transmission electron microscopy of conductive filaments in NiO resistance random access memory and its analysis

Abstract: We used thermal oxidization at various temperatures to prepare NiO/Pr-Ir for use in resistance random access memory (ReRAM) samples. In-situ transmission electron microscopy (TEM) was used to investigate the forming process of these ReRAM samples, where a needle-shaped top electrode of Pt-Ir was attached to the NiO/Pt-Ir ReRAM layer. The forming voltage initializing the NiO layer increased at an oxidization temperature of between 200 and 400 C. In this process, conductive bridges, which are thought to be condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The CF contained less oxygen than the bulk of the oxide (Fig. 15c-d) [47], and its diameter decreased by reducing the current. However, the subsequent RESET was not achieved because the oxygen liberated during electroforming escaped into the vacuum.…”
Section: In-situ Tem Of Filamentary Oxide Rerammentioning
confidence: 99%
“…The CF contained less oxygen than the bulk of the oxide (Fig. 15c-d) [47], and its diameter decreased by reducing the current. However, the subsequent RESET was not achieved because the oxygen liberated during electroforming escaped into the vacuum.…”
Section: In-situ Tem Of Filamentary Oxide Rerammentioning
confidence: 99%
“…In addition to perovskite-type ReRAMs [37][38][39] and devices based on binary oxides, [40][41][42][43][44][45][46] many reports on CBRAMs have appeared in recent years. [47][48][49][50][51][52][53] In one example, the dynamic growth and rupture of a Cu CF was confirmed during a switching cycle.…”
mentioning
confidence: 99%
“…To investigate the switching operation in real space, in-situ transmission electron microscopy (TEM) [25][26][27][28][29][30] has been applied to ReRAMs of various solid electrolytes. [31][32][33][34] Fujii et al 31,32 dynamically observed the growth and rupture of a conductive filament made of Cu in the Cu-Ge-S layer deposited on a needle-shaped Pt-Ir electrode.…”
mentioning
confidence: 99%